A plurinational transformation: an entanglement between change and continuity. (March 2023) - Rodriguez Alvarez, Gloriana
The persistence of a broad coalition of social movements, including Indigenous-led protests in the 1990s, the War on Gas, War on Water and the election of Evo Morales, contributed to a Plurinational Constitution in 2009. The result was a profound reframing of the social contract, enshrining legal, political and social pluralism. Nevertheless, the extent to which these measures have led to an improvement is still debated. For this reason, based on 22 interviews in La Paz and Sucre with former Constituent Assembly members from 2017 to 2019, this article examines the role of social movements in contesting the status quo . Second, it explores whether the pluralistic measures have changed the situation of Indigenous peoples and decolonised the governance model.